2022
DOI: 10.3389/fninf.2022.807584
|View full text |Cite
|
Sign up to set email alerts
|

Viability Study of Machine Learning-Based Prediction of COVID-19 Pandemic Impact in Obsessive-Compulsive Disorder Patients

Abstract: BackgroundMachine learning modeling can provide valuable support in different areas of mental health, because it enables to make rapid predictions and therefore support the decision making, based on valuable data. However, few studies have applied this method to predict symptoms’ worsening, based on sociodemographic, contextual, and clinical data. Thus, we applied machine learning techniques to identify predictors of symptomatologic changes in a Spanish cohort of OCD patients during the initial phase of the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Other models were also produced on a regular basis that predicts and categorized future occurrences using machine learning methodologies such as support vector machines, random forests, and artificial neural networks. [17]. Studies on the effects of the pandemic and associated issues on student mental health as a result, the goal of this project is to employ a carefully designed machine learning method, using SVM, to predict anxiety using real-world data from COVID-19 and to investigate how the lockdown affects students' mental health, social lives, and academic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other models were also produced on a regular basis that predicts and categorized future occurrences using machine learning methodologies such as support vector machines, random forests, and artificial neural networks. [17]. Studies on the effects of the pandemic and associated issues on student mental health as a result, the goal of this project is to employ a carefully designed machine learning method, using SVM, to predict anxiety using real-world data from COVID-19 and to investigate how the lockdown affects students' mental health, social lives, and academic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis of already existing scientific works showed that not all works can be used in practice to give a good result. After all, the works are mainly focused on one type of mental problem [25] or have a strong dependence on the location of a person, his age, or a certain situation in a given location (for example, a pandemic) [26].…”
Section: Introductionmentioning
confidence: 99%